The Promotional Management Of Salaf Islamic Boarding Schools In Increasing Animo of New Students: Manajemen Promosi Pondok Pesantren Salaf: Analisis dan Pengaruhnya Dalam Meningkatkan Animo Santri Baru - wakit , Saipul; Zaharuddin M; Dasep Supriatna; Margiono Suyitno (Halaqa: Islamic Education Journal, 2023)
As Islamic boarding schools grow and develop quantitatively, it certainly has a positive impact on society, namely that there are more and more choices of places to study Islam. However, from the negative side, as the number of Islamic boarding schools increases, there will be practices of competing with each other to gain influence and trust from the community. Therefore, the existence of Islamic boarding schools cannot be separated from elements of society who act as students or users. If the public is not interested in the Islamic boarding school, it will certainly have an impact on the sustainability and resilience of the Islamic boarding school. These conditions certainly require Islamic boarding schools to make efforts so that people are interested and willing to study at Islamic boarding schools. This effort is of course through promotion to the wider community using various methods, methods, media and requires good public relations. Therefore, this research specifically analyzes efforts, media, methods and sales marketing strategies to attract the interest of new students to study at Islamic boarding schools. Through qualitative research methods, researchers uncover and analyze Islamic boarding school efforts in carrying out promotions. Data collection techniques include observation, in-depth interviews and digging up documents from informants and research locations to obtain credible data and results.